Constitutional rights of the Fayli Kurds in Iraq - Dr, Rubar Majid Ahmad Ahmad (Sulaimani Journal for Humanities, 2024)
The fact that the Fayli Kurds, as a national and sectarian minority, are a Kurdish tribe residing in some Iraqi governorates and border regions between Iraq and Iran, and that they use the Elamite Kurdish dialect, is a significant issue. The central problem addressed in this research is that members of this minority have faced a long history of unjust persecution. For example, prior to the promulgation of the Iraqi Constitution in 1925, the Iraqi Nationality Law No. (42) of 1924 was issued retroactively to the date of implementation of the Treaty of Lausanne on August 6, 1924. This law categorized the indigenous Fayli Kurdish population as foreigners, leading to class divisions in Iraq and violating Article (6) of the 1925 Constitution, which stipulated that no discrimination between Iraqis was permissible for any reason. This law, however, deprived them of Iraqi nationality on the basis of their foreign status, casting doubt on their loyalty and national identity. Furthermore, the Fayli Kurds were subjected to a series of crimes against humanity, such as forced deportation. Forced displacement, and successive Iraqi constitutions and governments have been negligent in addressing the issue of the Faili Kurds, even the 2005 constitution did not mention them. Despite the Iraqi parliament's recognition of the crimes committed against them, such as genocide, and the issuance of several decisions by the Supreme Federal Court in Iraq to support the rights of the Faili Kurds, they have not enjoyed their constitutional rights, which they have been deprived of.
Keywords: Historical roots; deprivation of nationality; deportation; forced displacement; constitutional rights; forced displacement; deprivation of citizenship; restoration of identity; deprivation of property